Quality of life and habitual physical activity in children with cerebral palsy aged 5 years: A cross-sectional study - Keawutan, P.; Bell, K.; Oftedal, S.; Davies, P.; Ware, R.; Boyd, Roslyn (Pergamon Press, 2018)
Objective: To compare quality of life (QOL) according to ambulatory status and to investigate association with habitual physical activity (HPA) in children with cerebral palsy (CP) aged 5 years. Methods: Fifty-eight participants were classified using Gross Motor Function Classification System(GMFCS) as level I = 33, II = 8, III = 6, IV = 3 and V = 8 and assessed for motor function using 66-item Gross Motor Function Measure (GMFM-66). Participants wore an ActiGraph® triaxial accelerometer for 3 days to measure HPA. Parents completed the parent proxy Cerebral Palsy Quality of Life questionnaire for Children (CP QOL-Child). Linear regression analyses were performed. Results: Ambulant children with CP (GMFCS I–III) had better parent-reported QOL than non-ambulant children (GMFCS IV–V) in domains of feelings about functioning (mean difference (MD) = 20.0; 95% confidence interval (CI) = 11.7, 28.2), participation and physical health (MD = 14.5; 95%CI = 4.7, 24.4), and emotional well-being and self-esteem (MD = 12.5; 95%CI = 4.8, 20.1). HPA was not associated with QOL domains after controlling for motor function. GMFM scores accounted for 39% of variation for feelings about functioning domain (MD = 0.4; 95%CI = 0.2, 0.6). Conclusions: In children with CP aged 5 years, HPA was not associated with parent-reported QOL. Gross motor function contributed to QOL domains of feelings about functioning.